LANGUAGE, CULTURE, AND CURRICULUM: DESIGNING EFFECTIVE MATERIALS FOR TEACHING UYGHUR - Gulnisa Nazarova (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
What are the best resources for learning a language? Many cite interaction with native speakers, media, and apps like Duolingo or Anki. While valuable, these tools are best complemented by comprehensive textbooks, which provide the structure and depth essential for mastering less-commonly taught languages. Textbooks designed with authentic materials and cultural context play a pivotal role in language learning, especially when we talk about less commonly taught languages.